1991
DOI: 10.1021/bi00236a031
|View full text |Cite
|
Sign up to set email alerts
|

Shape and lipid-binding site of the nonspecific lipid-transfer protein (sterol carrier protein 2): A steady-state and time-resolved fluorescence study

Abstract: Shape and lipid binding site of the nonspecific lipid-transfer protein (sterol carrier protein 2): a steady-state and time-resolved fluorescense study Gadella, T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 65 publications
(101 reference statements)
3
21
1
Order By: Relevance
“…SCP-2 (44). The range in light scatter distribution of 1 mM SCP-2, from 25-58 Å, was also consistent with the fact that SCP-2 is not perfectly spherical but is somewhat ellipsoidal as previously determined by fluorescence techniques (44,61). Thus, the light scatter data demonstrated that both unliganded SCP-2 and liganded SCP-2 were not aggregated or in multimeric form at the millimolar concentrations necessary for 13 C NMR experiments.…”
Section: Discussionsupporting
confidence: 88%
“…SCP-2 (44). The range in light scatter distribution of 1 mM SCP-2, from 25-58 Å, was also consistent with the fact that SCP-2 is not perfectly spherical but is somewhat ellipsoidal as previously determined by fluorescence techniques (44,61). Thus, the light scatter data demonstrated that both unliganded SCP-2 and liganded SCP-2 were not aggregated or in multimeric form at the millimolar concentrations necessary for 13 C NMR experiments.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, mammalian tissues contain a 58-kDa protein, SCP-x, sharing the same C-terminal 123 amino acid sequence (13.2 kDa) as found in SCP-2 (42). The SCP-x is localized exclusively in peroxisomes (13,38,39) and, furthermore, displays fatty acylCoA thiolase activity, an enzyme involved in ␤-oxidation of fatty acids (42).…”
Section: Discussionmentioning
confidence: 99%
“…By taking advantage of the fact that 13-kDa SCP-2 contains only a single Trp residue (amino acid position 50) and no tyrosines, the intrinsic fluorescence properties of Trp 50 could be utilized to ascertain the location of the Trp 50 and the overall shape, and hydrodynamic radius of 13 kDa SCP-2 [31;50]. Steady state fluorescence emission spectra as well as Stern-Volmer quenching (acrylamide and iodide) studies revealed that the Trp 50 was located in a hydrophobic locus.…”
Section: Fluorescencementioning
confidence: 99%
“…Steady state fluorescence emission spectra as well as Stern-Volmer quenching (acrylamide and iodide) studies revealed that the Trp 50 was located in a hydrophobic locus. According to time-resolved fluorescence spectroscopy of Trp 50 , 13-kDa SCP-2 (isolated from bovine liver) exhibited a rotational correlation time of 15 ns [50]. In contrast, phase-and modulation-resolved fluorescence spectroscopy of Trp 50 in human recombinant 13-kDa SCP-2 showed a significantly smaller rotational correlation time near 7.8 ns, consistent with SCP-2 being a globular protein with a hydrodynamic radius of 20.5 Å, diameter 41 Å [31].…”
Section: Fluorescencementioning
confidence: 99%